A STUDY OF THE ESSENTIAL ROLE OF THE ELECTION COMMISSION IN HOLDING ALL MAJOR ELECTIONS IN INDIA SIMULTANEOUSLY - Kumar, Vijay; Anand, Ashutosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India’s democratic structure thrives on its vibrant electoral process that enables citizens to actively shape governance at every level. Over 400 elections to the Lok Sabha and state assemblies since independence have demonstrated the Election Commission of India’s commitment to fairness and transparency. However, the nature of separate and frequent elections has led to discussions on the need for a more efficient system. This has revived interest in the concept of "one nation, one election". This idea of ​​"one nation, one election", also known as simultaneous elections, proposes holding elections to the Lok Sabha and state assemblies simultaneously. This would allow voters to cast their votes for both levels of government in their constituencies on the same day, although voting may be held in multiple phases across the country. The approach of aligning these electoral timelines aims to address the challenges associated with the management of elections, reduce costs and minimise disruptions in work due to frequent elections.